Rethinking Teaching Strategies: Considerations for Promoting Equity, Diversity, And Inclusion - binti Salleh, Rosmalily binti Salleh (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
Equity, diversity, and inclusion (EDI) significantly enhance educational opportunities for all learners and prepare socially and economically inclusive societies. Classrooms are increasingly diverse as difference is an essential part of human life, in the past, current, and future. The ideas of teaching for diversity, equity, and inclusion complement each other and enhance educational opportunities for all pupils when simultaneously engaged. This study examines primary school teachers’ views on their continuous professional development (CPD) needs to ensure all pupils are supported for quality education. Studies implemented mainly focus on the perspectives and beliefs of mainstream or special education teachers about inclusive education. Yet, teachers' voices about their own CPD needs to improve their inclusive practice remained overlooked. This study, therefore, adopts a qualitative approach where 76 respondents were purposely sampled from five national schools in Malaysia. Semi-structured interviews of focus groups and individuals were implemented; with 10 classroom observations executed before the individual interviews. Data were analysed thematically using qualitative analysis software. The study shows that teachers view CPD as a strategy to drive change and improve teachers’ practice as professionals and effective CPD activities focus on addressing the belief and knowledge of teachers in improving their teaching strategies to tackle all pupils. This article provides a useful guide for school leaders in planning, implementing, and culture the CPD activities. Infusing EDI in CPD is essential for promoting an inclusive learning environment and is conducive to ensuring that all pupils could achieve their optimum potential with teachers’ enhanced teaching strategies.